THE EFFECT OF USING ORAL QUIZZES ON STUDENTS’ SPEAKING SKILL - Nurul Dwianta, Alya; Talib, Ahmad; Fauzan, Muh. Miftah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
The goal of the study is to determine how taking oral quizzes affects students' ability to speak. Pre-experimental design with a single group pretest-posttest was employed in this study. The SMAN 4 Makassar second grade pupils for the academic year 2023–2024 served as the research population. Purposive sampling was used in this study, and the sample consisted of 20 students from Class XI.10 at SMAN 4 Makassar. The study's conclusions showed that after receiving treatment, students' speaking abilities significantly improved. The difference in mean scores between the pre-test (60.75) and post-test (69.20) indicates this. Students' speaking skills were able to increase as a result of the oral quiz technique, as evidenced by the mean score of the students. Students may be required by this method to actively participate in their education, particularly when it comes to speaking skills. Additionally, teachers can utilize this tactic as a substitute or a guide to pique students' interest in the learning process..Key words-- Speaking Skill; Oral Quizzes; Strategy